Spectrophotometric Estimation of Oseltamivir in Pharmaceutical Formulations - Kiran Kumar, V.; Raju, N.Appala (Asian Journal of Chemistry, 2010)
Three simple, accurate, rapid and sensitive methods (A, B and C) have been developed for the estimation of oseltamivir in its pharmaceutical dosage form. The method A is based on the formation of orange red coloured chromogen, due to reaction of oseltamivir with p-dimethyl amino cinnamaldehyde (PDAC) reagent in methanol, which exhibits λmax at 530 nm. Method B is based on the reaction of oseltamivir with 4-aminophenazone (4-AP) in the presence of sodium periodate to form a intense violet coloured chromogen, which shows maximum absorbance at 545 nm. The method C is based on the formation of blood red coloured chromogen with ferric chloride and 1,10-phenanthroline which shows absorption maximum at 512 nm. The absorbance-concentration plot is linear over the range of 1-7 mcg/mL for method A, 5-50 mcg/mL for method B and 1-15 mcg/mL for method C. Results of analysis for all the methods were validated statistically and by recovery studies. The proposed methods are economical and sensitive for the estimation of oseltamivir in bulk drug and in its formulations.